The Impact of Post‐thyroidectomy Paresis on Quality of Life in Patients with Nodular Thyroid Disease. (11th June 2019) - Sorensen, Jesper Roed; Printz, Trine; Iwarsson, Jenny; Grøntved, Ågot Møller; Døssing, Helle; Hegedüs, Laszlo; Bonnema, Steen Joop; Godballe, Christian; Mehlum, Camilla Slot
Abstract : Objective: To investigate the impact of postoperative paresis on disease‐specific quality of life (DSQoL) after thyroidectomy in patients with benign nodular thyroid disease. Study Design: Observational study. Setting: University hospital. Subjects and Methods: Patients were evaluated before and 3 weeks and 6 months after surgery in an individual prospective cohort study using videolaryngostroboscopy (VLS), voice range profile, voice handicap index (VHI), multidimensional voice program, maximum phonation time (MPT), and auditory perceptual evaluation. Changes in DSQoL were assessed by the Thyroid‐specific Patient‐Reported Outcome measure. Cohen's effect size was used to evaluate changes. Results: Sixty‐two patients were included, 55 of whom completed all examinations. Three weeks after surgery, a blinded VLS examination showed signs of paresis of either the recurrent laryngeal nerve or the external branch of the superior laryngeal nerve (RLN/EBSLN) in 13 patients (24%). A paresis corresponded to a 12 ± 28 point increase in VHI ( P =. 002) and was associated with a significant 4.3 ± 7.5 semitone decrease in the maximum fundamental frequency ( P <. 001) and a 5.3 ± 8.2 dB reduction in maximum intensity. Further, it was associated with a 4.5 ± 11.2 second reduction in MPT ( P =. 001) and an increase of 0.40 ± 1.19 in grade, 0.42 ± 1.41 in roughness, and 0.36 ± 1.11 in breathiness. Signs of postoperative RLN/EBSLN paresis correlated with an 11.0‐point ( P =. 02) poorer improvement in goiter symptoms at both 3 weeks and 6 months after surgery. Conclusion: Signs of RLN/EBSLN paresis after thyroidectomy were associated with less pronounced improvement in goiter symptoms in patients with thyroid nodular disease. However, thyroidectomy was associated with an overall improved DSQoL by 6 months after surgery.